PHENOMENA OF WELLNESS TOURISM: A CASE STUDY OF THE ACTUALITY OF WELLNESS TOURISM PARTICIPANTS IN SAYAN VILLAGE - Rahjasa, Putu Surya Laksana; Naur, Laurensius (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2024)
This research aims to explore the authentic value of wellness tourism from several points of view, namely from the tourism sector, tourists, stakeholders, and experts. This research describes wellness tourism in terms of the perspective and image of health tourism. This research uses qualitative methods by examining the recent wellness tour phenomenon. The key informants in this research are stakeholders and psychologists. The main informants in this research are domestic and foreign tourists who carry out wellness tourism activities in Ubud, Bali. The results of this research provide positive results from a wellness tour perspective on the image of wellness tours.